Mathematical Modeling and Simulation of Multi Loop Pilot Plant - Mohite, Saurabh U; Patil, Abhishek P; Patil, Shreyas D; Pawar, D. N. (International Journal of Computer Sciences and Engineering, 2019)
This paper focuses on the identification and modeling of the pilot plant of the department. For this work, four loops of pilot plant are considered. Level loop, flow loop, cascade loop and temperature loop. Transfer function for level loop is derived by using process reaction curve and the flow loop transfer function is derived using dynamics of Control valve and specifications of process plant components. Cascade Loop is the series combination of flow and level loops. The temperature system is nonlinear in nature due to three variables initial temperature, input flow and heat supplied by heater. Hence different control schemes are considered to control the various conditions i.e. batch process, continuous Process with constant input and output flow. Also Feedback linearization is used for as a unique control scheme. Pilot plant being a multi loop system, there is interaction between the loops such as level and temperature loop. The interaction is eliminated with the help of decoupler and relative gain array to obtain non-interacting level and temperature loops such that the temperature can be controlled without affecting the level parameter of the system.